Production and Characterization of Keratin/Tragacanth Gum Nanohydrogels for Drug Delivery in Medical Textiles - Mansouri Shirazi, Nazanin; Eslahi, Niloofar; Gholipour-Kanani, Adeleh (Frontiers in Materials, 2021)
Keratin protein has been applied for biomedical applications due to its biocompatibility, biodegradability, mechanical resistance and bioavailability. Tragacanth gum (TG) as a polysaccharide-based biopolymer has wound healing and antimicrobial properties. In this study, keratin was extracted from protein-based chicken feather by using reduction hydrolysis (sodium sulfide) and nanogels of keratin and TG composites at different ratios were produced by using chemical cross-linking method. Then, cinnamon (5% and 10%) as an antibacterial herbal extract was added to the nanogels and coated on cotton fabric. The morphology and size of the composite nanogels, chemical structure, biological and antibacterial properties were evaluated. According to DLS results, TGK2:1 (ratio of TG to keratin=2:1) had the minimum size (80 nm) and PDI (0.1) and therefore this sample was chosen as the optimum one. FESEM and TEM images showed semi-spherical shape of the produced nanogels. FTIR spectra revealed the possible hydrogen bonding between the components and formation of disulfide bonds after addition of hydrogen peroxide was confirmed by XPS. After loading cinnamon into the nanogels, an increase in size was observed from 80 nm for free-nanogel to 85 nm and 105 nm for 5% and 10% extract-loaded nanogels, respectively. Besides, more cinnamon was released from the treated fabrics by increasing time and cinnamon concentration. The antibacterial test exhibited good antibacterial properties against both gram-positive and gram-negative bacteria. Finally, MTT assay approved the biocompatibility of the produced nanogels for potential use in medical textiles.